Energy and Water Consumption Variability in School Buildings: Review and Application of Clustering Techniques - Ricardo M. S. F. Almeida (2015)
In developed countries, the building sector is responsible for a very significant share of the total energy consumption. School buildings, because they are places where children are educated and learn to become active members of the society, should be a good example of an efficient use of energy and water. In this study, data of the energy and water consumption of 23 Portuguese schools and their main building characteristics and properties were gathered. This information was normalized to homogenize the data set and then analyzed using advanced clustering techniques. The results show a significant variability in the consumption of different schools, even with similar characteristics, suggesting that the user behavior plays an important role in their efficiency. The complete linkage and Ward's clustering methods were applied, both produced three clusters, and reference values for electricity and water consumption were defined. (C) 2014 American Society of Civil Engineers.